A polymorphism in porcine miR-22 is associated with pork color - Wang, Han; Shen, Zhonghao; Huang, Ruihua; Zhao, Ayong; Jiang, Jiani; Li, Pinghua; Zhou, Xiaolong; Yang, Songbai; Hou, Liming (Frontiers in Veterinary Science, 2022)
MicroRNAs (miRNAs) are posttranscriptional regulators that play key roles in meat color regulation. Changes in miRNA expression affect their target mRNAs, leading to multifunctional effects on biological processes and phenotypes. In this study, a G > A mutation site located upstream of the precursor miR-22 sequence in Suhuai pigs was significantly correlated with the meat color parameter a*(redness) of the porcine longissimus dorsi (LD) muscle. AA genotype individuals had the highest average meat color a* value and the lowest miR-22 level. When G > A mutation was performed in the miR-22 overexpression vector, miR-22 expression significantly decreased. Considering that Ca2+ homeostasis is closely related to pig meat color, our results further demonstrated that ELOVL6 is a direct target of miR-22 in pigs. The effects of miR-22 on skeletal muscle intracellular Ca2+ were partially caused by the suppression of ELOVL6 expression.